2020
DOI: 10.2174/1874944502013010415
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Adolescent/Youth Sexual and Reproductive Health Communication: The Case of Secondary and Preparatory School Students in Fiche Town, Oromia Regional State, Ethiopia

Abstract: Background: Adolescence/youth is a continuum of physical, cognitive, behavioral, and psychosocial development. Due to a lack of comprehensive knowledge regarding sexual and reproductive health, adolescents face a number of problems. Clear family communication of reproductive health issues often leads to increased awareness of reproductive health matters and reduces risky behaviors and its consequences in adolescent populations. Objective: To assess parent-adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In this study, it was found that parent-adolescent discussion on RH issues was 55.2% which was in line with studies conducted in Boditi (40.7%) [ 19 ] and Yirgalem (59.1%) [ 20 ] Southern Ethiopia. But It was higher than the results from the previously conducted research in Debre Markos, East Gojjam, Ethiopia (28.9%) [ 23 ], in Awabel, East Gojjam, Ethiopia (25.3%) [ 24 ], in Fiche, North Showa, Ethiopia (31.2%) [ 17 ], in Harar, Eastern Ethiopia (28.76%) [ 21 ], in Rwanda (29%) [ 25 ]. This discrepancy could be attributed to the differences in sample sizes in the studies and sociodemographic differences in the regions.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…In this study, it was found that parent-adolescent discussion on RH issues was 55.2% which was in line with studies conducted in Boditi (40.7%) [ 19 ] and Yirgalem (59.1%) [ 20 ] Southern Ethiopia. But It was higher than the results from the previously conducted research in Debre Markos, East Gojjam, Ethiopia (28.9%) [ 23 ], in Awabel, East Gojjam, Ethiopia (25.3%) [ 24 ], in Fiche, North Showa, Ethiopia (31.2%) [ 17 ], in Harar, Eastern Ethiopia (28.76%) [ 21 ], in Rwanda (29%) [ 25 ]. This discrepancy could be attributed to the differences in sample sizes in the studies and sociodemographic differences in the regions.…”
Section: Discussionmentioning
confidence: 62%
“…Discussion on RH issues: parents who have ever discussed at least two RH issues (contraception, STIs/HIV/AIDS, sexual intercourse, unwanted pregnancy, avoiding premarital sex, condom, changes during puberty, and menstrual cycle) with adolescents living in the household were considered to have discussed on RH issues [ 17 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations